The United Nations Security Council Resolution 1325 (Unscr 1325) and The Challenges of Women Participation in Peace Building and Conflict Resolution in Nigeria: Critical Analysis - Ekpe, Dickson E. (Advances in Social Sciences Research Journal, 2020)
In 31 October, 2000, the United Nations Security Council adopted and signed SC Resolution 1325 on Women Peace and Security. Resolution 1325 recognizes that civilian, particularly women and children are the worst affected by conflict. Resolution 1325 call for women participation in conflict prevention and resolution initiative, the integration of gender perspective in peace building, peace keeping mission and the protection of women in regions of conflict. The resolution reaffirms the important role of women in the prevention and resolution of conflicts, peace negotiations, peace-building, peace keeping, humanitarian response and in post-conflict reconstruction; stressing the importance of equal participation in peace and security. In Africa, women participation in policy making, peace building and conflict resolution is still faced with setbacks despite the passing of the SCR 1325 two decades ago. Findings from this study has shown that, women have been subjected to domination by men as a result of persisting cultural stereotypes, abuse of religious and traditional practices, patriarchal societal structures in which economic, political and social power are dominated by men while women played the role of followers of male decision-makers. The study identifies such challenges for a change or reforms them. The paper reviewed many of the extant studies on the role and potentials of women in peace building and conflict resolution. Analyzing those challenges inhibiting the participation of women in peace process. The paper adopted the qualitative approach whereby data collected from secondary sources were reviewed, explained and analyzed within the purview of the study. The paper conclude, the views that bringing women into the peace process, as participation of women makes it sustainable and reduces possibility of inadequate outcome or failure of the entire process, may be an illusion. Unless the women are economically and politically empowered, as one of the outstanding equality of peace-makers or negotiators is the amount of political and economic influence they possessed. Only elite centric gender blind composition of negotiation and peace process team cannot ensure sustainable peace process as there could be no peace with one side so disadvantaged.